Analysis of Fine Motor Development of Children Aged 4-5 Years in KB Cendekia Bapangan Through Pottery Formation Play Activities - Nurmala, Akhidah; Zulfahmi, Muhammad Nofan (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2024)
Pottery is one of the traditional handicrafts made of clay that is shaped in such a way and then heated until it becomes hard. This clay pottery forming game can help children's imagination to make a desired object from clay play. This study aims to determine the fine motor development of children through pottery playing activities. The research method applied in writing this article is qualitative method. The results of this study confirm the importance of paying attention to children's fine motor development, especially by parents and teachers. Fine motor development, which involves coordinating small muscles in movements such as writing and buttoning a shirt, is essential for everyday tasks. One effective method to support fine motor development is through the medium of play, especially the manufacture of pottery from clay. This activity not only improves fine motor skills, but also develops the child's creativity and sensory experience. Clay manipulation requires precise hand movements, which strengthen eye-hand coordination and dexterity. In addition, working with clay encourages children to use their imagination, provides rich sensory stimulation, and allows emotional expression through art. To integrate pottery activities into early childhood education, teachers and parents can introduce structured pottery sessions, provide free playtime, incorporate thematic projects, encourage collaborative projects, and showcase children's work to celebrate their achievements. Thus, the use of clay in early childhood learning becomes a fun and effective way to support fine motor development and other aspects of development.